Next Generation Sequencing and Lysosomal Dysfunction: Novel mutations associated with Neurodegenerative disorders. - Encarnação, Marisa (2019)
Lysosomal Storage Disorders (LSD) are a group of inherited metabolic diseases characterized by a wide range in phenotypes and clinical variability. The diagnosis is often difficult and time consuming, with multiple tests/samples being required before a definitive diagnosis is reached. Next Generation Sequencing (NGS) is changing this scenario by allowing variant assessment at a large scale in a single run. The aim of this work was to develop an NGS-based workflow for the identification of LSD-causing variants. We designed a panel including exons and intronic flanking regions from 96 genes involved in lysosome homeostasis and function. The workflow was performed using a Sureselect protocol followed by sequencing in an Illumina MiSeq® platform. For alignment and variant anotation softwares Surecall and wANNOVAR were used. Validation of this custom-targeted panel was performed in 5 blind controls. For the studied cases, we could reach molecular diagnosis consistent with the clinical and biochemical diagnosis in 7 patients, corresponding to a diagnostic rate of 67% (7/11). For the undiagnosed patients, an extended custom panel composed also of autophagy modulators and other genes involved in lysosome biogenesis will be tested. From our first results we would like to highlight the detection of a novel frameshift mutation in the GM2A gene, which is associated with the extremely rare AB variant of Gangliosidosis, biochemically and clinically undistinguishable from the other two (Tay Sachs and Sandhoff Diseases). Also noteworthy, we were able to find out the molecular defect of a patient with a general clinical suspicion of Neuronal Ceroid Lipofuscinosis (CLN). From the 14 possible genes associated to these disorders, we detected the molecular defect in a single analysis. In fact, we identified a novel missense variant in the MFSD8 gene, reaching the diagnosis of a CLN7. Additionally, novel mutations in GLA, GALC, and NAGLU genes were found. We have also started a functional analysis to investigate the impact of two novel splicing mutations (GNPTAB and ARSB) and two novel missense mutations in NPC1 gene.